Power and religiosity in a post-colonial setting: Sinhala Catholics in contemporary Sri Lanka - Stirrat, R. (Cambridge studies in social and cultural anthropology, 1992)
Over the past few decades a series of Catholic shrines have sprung up in Sri Lanka which draw hundreds of pilgrims. Although best known as centres for the exorcism of the demonically possessed, their miraculous efficacy also extends to helping people find jobs and preferment, and to alleviating suffering. Dr Stirrat, who has worked in Sri Lanka over a long period, is interested both in how people behave at the shrines, and in the historical and social contexts in which the shrines have appeared. He argues that an understanding of their religious importance is intricately connected with power, religious and political. This view challenges the conventional distinction between 'religion' and 'politics', and accordingly, religious suffering is seen as a complex metaphor linking together various social domains and a means through which conflicts over power and authority can be expressed.